Technology in action complete - Evans, Alan; Martin, Kendall; Poatsy, Mary Anne (Pearson, 2016)
Explore, discover, and experience technology with the immersive and adaptive Technology in Action, the book that uses technology to teach technology! This is a learning system that pushes the envelope of what is possible in technology, and what is helpful in teaching. It is a system that fits the way students are learning today.